Cultural and Economic Factors in the Fertility of Thai Women - Hogan, Dennis P. (Allahabad, India : Papers of east-west population institute, 1987)
Study focusses on slum dwellers in Visakhapatnam, Andhra Pradesh, India.
Includes bibliographical references (p. [187]-198).
Keywords: Women; India -- Vishakhapatnam; India -- Vishakhapatnam